Uptake of Travel Health Services by Community Pharmacies and Patients Following Pharmacist Immunization Scope Expansion in Ontario, Canada - Sherilyn K. D. Houle; Kristina Kozlovsky; Heidi V. J. Fernandes; Zahava Rosenberg-Yunger (MDPI AG, 2019)
In December 2016, pharmacists in Ontario, Canada with authorization to administer injections saw an expansion in their scope from a restriction to the influenza vaccination only to now including an additional 13 vaccine-preventable diseases, largely those related to travel. It was uncertain whether this change in scope would see sufficient uptake, or translate to a corresponding expansion in other travel health service offerings from community pharmacies. In October/November 2017 a survey was conducted of all licensed community pharmacists in Ontario, followed by semi-structured interviews with 6 survey respondents in June 2018. A web-based survey of members of the public from a single region of the province was also conducted in September 2018 to assess uptake of expanded vaccination services. Broad variability in uptake of these services was noted, ranging from the dispensing of travel-related medications and vaccinations only through to vaccine administration and prescribing under medical directive; however, uptake was generally at the lower end of this spectrum. This was evidenced by 94% of pharmacists reporting administering fewer than 10 travel vaccinations per month, fewer than 10% of patients reporting receiving a travel vaccine administered by a pharmacist, and a maximum of 30 pharmacies (of nearly 6000 in the province) designated to provide yellow fever vaccinations. Fewer than 1 in 3 pharmacists reported performing some form of pre-travel consultation in their practice, often limited to low-risk cases only. Barriers and facilitators reported were similar for these services as they were for other non-dispensing services, including insufficient time to integrate the service into their workload, perceived lack of knowledge and confidence in travel health, and low patient awareness of these new services available to them through community pharmacies.